Cultivation of Parasitic Leptospires: Effect of Pyruvate - Johnson, R. C. (1973)
Sodium pyruvate (100 μg/ml) is a useful addition to the Tween 80-albumin medium for the cultivation of parasitic serotypes. It is most effective in promoting growth from small inocula and growth of the nutritionally fastidious serotypes.